Optimal concentration of potassium iodide to reduce the black staining of silver diamine fluoride - Palinee Detsomboonrat; Panatsaya Thongmak; Phattaramon Lertpayab; Watsharapol Aiemsri; Sireerat Sooampon (Elsevier, 2022)
Background/purpose: Potassium iodide (KI) is used for reducing the degree of black staining occurred after silver diamine fluoride (SDF) application. However, the optimal KI concentration remains unknown. This study aimed to identify the optimal concentration of KI that effectively reduces black staining after SDF application. Materials and methods: Twenty-four extracted teeth with similar pattern of carious lesions were assigned into 6 groups as follows: 1) SDF only, 2) SDF+7.5%KI, 3) SDF+10%KI, 4) SDF+15%KI, 5) SDF+20%KI, and 6) SDF+saturated KI. The KI solution was applied immediately after SDF application. Tooth images were obtained for color measurement at different time points as followed; before SDF application, immediately after SDF application, immediately after KI application, 1, 3, 7 and 14 days after SDF+KI application. The photographs were analyzed for mean gray value using the ImageJ program. Results: The KI groups demonstrated a dose-dependent significant immediate reduction in black staining after KI application, except the saturated KI group. The teeth in the 20% KI group had the highest Δ mean gray value compared with other groups immediately after KI application, whereas a reduction in black staining in the saturated KI group appeared 1 day after KI application. The Δ mean gray value in all groups decreased over time. After 7 and 14 days, the reduction in black staining was not clearly different between KI groups. Conclusion: KI application was able to reduce the degree of black staining in a dose-dependent manner, but the subsequent color change was minimal over the period of 14 days.